2022
DOI: 10.1039/d2ay01040b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of neomycin-derived fluorescent carbon dots for selective detection of Fe3+ ions

Abstract: The first-ever neomycin antibiotic-based carbon dots (Neo-CDs) were synthesized via low-cost, eco-friendly, and a single-step hydrothermal method using neomycin as a single precursor. The as-prepared Neo-CDs exhibited strong and stable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…As the Fe 3+ ion has a half-filled 3d orbital, it could effectively bind with the various functional groups such as −OH and −NH 2 present on the surface of NCQDs to form a coordination complex. The fluorescence quenching through the nonradiative transition process takes place by the electron transfer from the excited state (conduction band) of NCQDs to the half-filled 3d orbital of the Fe 3+ ion, a photoinduced electron transfer (PET) process. , The fluorescence decay parameters are shown in Table , and the decay curves of NCQDs in the presence and absence of Fe 3+ ions are presented in Figure a. It was found that the average lifetime of NCQDs shifted from 3.01 to 2.31 ns on the addition of Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…As the Fe 3+ ion has a half-filled 3d orbital, it could effectively bind with the various functional groups such as −OH and −NH 2 present on the surface of NCQDs to form a coordination complex. The fluorescence quenching through the nonradiative transition process takes place by the electron transfer from the excited state (conduction band) of NCQDs to the half-filled 3d orbital of the Fe 3+ ion, a photoinduced electron transfer (PET) process. , The fluorescence decay parameters are shown in Table , and the decay curves of NCQDs in the presence and absence of Fe 3+ ions are presented in Figure a. It was found that the average lifetime of NCQDs shifted from 3.01 to 2.31 ns on the addition of Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…We have cited additional references within the Supporting Information [51–88] . The Supporting Information includes: 1.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…1 Heavy metals can negatively impact human health, as the metals are difficult to breakdown in living organisms and can become enriched through the food chain. Among heavy metal ions, iron ions (Fe 3+ ) are vital for enzyme catalysis, oxygen transport, and cellular metabolism; 2,3 However, the incidence of certain cancers and organ dysfunction can increase when organisms consume excessive amounts of Fe 3+ . 4 In addition, ionizing radiation is commonly utilized in various industries, such as agriculture, medicine, and national defense.…”
Section: Introductionmentioning
confidence: 99%